Wind-resistance performance of high-voltage isolating switches under typhoon conditions: A numerical simulation analysis. (October 2022) - Zhang, Chunying; Yang, Yangyang; Jia, Zhidong; Wang, Xilin
Highlights: Analyzed high-voltage isolating switch responses varying wind speed and direction. Calculated shape coefficients and validated empirical formula. Compared dynamic and static responses of high-voltage isolating switches. Breaking wind speed of insulator was 46.7 m/s at worst wind attack angle. Abstract: In recent years, typhoons have caused extensive damage to high-voltage isolating switches. To analyze the wind-resistance performance of isolating switches under typhoon, we used the fluid–structure coupling method to calculated the shape coefficients of the isolating switch. The static and dynamic responses of isolating switches under typhoon were also analyzed. Results show that the root of conducting rods and that of porcelain vase bore a high stress. The responses and shape coefficients varied considerably for different wind attack angles, and the most unfavorable wind attack angle was 180°. Comparing with response under static wind load, the dynamic response was more severe. At 180° angle of attack, the vibration frequency was 3.167 Hz, which is close to the first-order natural vibration frequency. The breaking wind speed of the insulator was 46.7 m/s. This research could serve as a reference for the wind resistance design and provide early risk warning for isolating switches.